2002
DOI: 10.1021/tx010156s
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Aflatoxin B1 Oxidation Products with Lysine

Abstract: Aflatoxin (AF) B(1) exo-8,9-epoxide hydrolysis yields AFB(1) dihydrodiol, which undergoes base-catalyzed rearrangement to, and is in equilibrium with, AFB(1) dialdehyde. We investigated the reaction of AFB(1) dialdehyde with albumin to generate a Lys adduct, previously characterized by others [Sabbioni, G., Skipper, P. L., Büchi, G., and Tannenbaum, S. R. (1987) Carcinogenesis8, 819-824; Sabbioni, G. (1990) Chem.-Biol. Interact. 75, 1-15]. Pronase digestion of bovine albumin serum treated with AFB(1) dialdehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 37 publications
4
77
0
Order By: Relevance
“…Although we did not measure the expression of GSTs in this particular study, previous studies have demonstrated that the level of GSTs in these cells are negligible (20). In the case of AFB 1 dihydrodiol, this metabolite can undergo a slow, base-catalyzed ring opening to a dialdehyde (7,31) that is capable of forming Schiff base adducts with protein amino groups, particularly lysine (16). Previous studies suggest that this type of reaction could be involved in the acute toxicity of AFB 1 (12).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although we did not measure the expression of GSTs in this particular study, previous studies have demonstrated that the level of GSTs in these cells are negligible (20). In the case of AFB 1 dihydrodiol, this metabolite can undergo a slow, base-catalyzed ring opening to a dialdehyde (7,31) that is capable of forming Schiff base adducts with protein amino groups, particularly lysine (16). Previous studies suggest that this type of reaction could be involved in the acute toxicity of AFB 1 (12).…”
Section: Discussionmentioning
confidence: 88%
“…Production of a C-6a monoalcohol, corresponding to reduction of the C-6a carbon of the dialdehyde, occurred at a much lower rate and the formation of the dialcohol was not rapid in these reactions (17). In a subsequent study, Guengerich and coworkers (16) clearly established a role of AFB 1 dialdehyde in the formation of protein adducts. Based on the rates determined for the various reactions, these author proposed that starting with AFB 1 -8,9-epoxide, the reactivity of the dialdehyde is linear over several hours.…”
Section: Introductionmentioning
confidence: 97%
“…Knowledge of AFB 1 metabolism suggests that additional protein adducts should be formed, and the differences in AF-albumin adduct concentration measured by ELISA and IDMS are therefore likely to be due to the presence of uncharacterized AF adducts. Spontaneous formation of the hemiacetal AFB 2a from AFB 1 or AFB 2 can be expected to yield protein adducts through reactions similar to that producing AF-lysine (19,20,28). Although significant human exposure to AFG 1 occurs, and this toxin can form both DNA and albumin adducts in rats (29), AFG 1 -lysine adduct formation has not been shown in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The only AFB 1 adduct structurally identified to date in enzymatically digested plasma albumin is AFB 1 -lysine (AF-lysine; refs. 14,19,20). This adduct has been measured by ELISA, high-performance liquid chromatography (HPLC) with fluorescence detection and more recently by isotope dilution mass spectrometry (IDMS; refs.…”
Section: Introductionmentioning
confidence: 99%
“…It is activated by oxidation to an epoxide, which is subsequently hydrolyzed to a vicinal dialdehyde, which in turn forms bidentate adducts with amines. [56,57] This toxicant also targets alkylation of DNA nitrogens, but the study of this latter reactivity is outside the current scope of the SEURAT-1 project.…”
Section: Alkylating Agentsmentioning
confidence: 99%